(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
Numerical investigation of supersonic turbulent flow with perpendicular injection of helium jet is considered. The algorithm of numerical solution is based on the third order of accuracy ENO scheme. The influence of k −ε model, k −ε with compressibility and Baldwin-Lomax’s model on shock wave structure of the flow, supersonic and subsonic zones, on formation of vortex (recirculation) structure in the subsonic zone near wall before and after the jet are investigated. Also, the geometry and flow parameters influence on the separation region near the wall and on the penetration depth of the jet are investigated. The quantitative and qualitative agreement of numerical results with Kramer and Rogers experimental data, particularly, the pressure on the wall was obtained.